Practices of internal control mechanisms in managing force account-related funds in Public secondary Schools: Experience from Meatu District Council, Tanzania - Juma, Sadru; Loisulie , Paul; Ali, Habibu (Papanda Publisher, 2024)
This study examined the internal control mechanisms for managing force account-related funds in public secondary schools in Meatu District Council, Simiyu region. Employing a qualitative approach and case study design, data were collected from 17 key stakeholders, including district officials and school heads, through semi-structured interviews and document reviews. Thematic analysis highlighted the importance of financial accountability and transparency in managing these funds. Key findings indicate that meticulous documentation, adherence to guidelines, and regular reporting are essential for fostering a transparent financial management system. The establishment of specialized committees, based on experience and qualifications, enhances oversight and management of projects. Additionally, active stakeholder involvement and detailed record-keeping promote community engagement and transparency, while regular internal audits reinforce accountability and regulatory compliance. The study concludes that effective management of force account-related funds in educational construction relies on strong financial accountability, transparent procedures, specialized oversight, and meticulous resource management, which together ensure efficient fund usage, improved project outcomes, and enhanced stakeholder trust.